Effect of Students’ Term and Educational Institution on the Arising of Indonesian Morphology-Syntactical Interference in ELLT - Nurhayati, Dwi Astuti Wahyu; Djatmika, Djatmika; Santosa, Riyadi; Wiratno, Tri (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
This research examines the two factors which effect on the raising of Indonesian morphology-syntactical interference. It aimed at delineating the potential effect of these two factors on the arising of Indonesian morphology-syntactical interference of undergraduate students majoring in English department of State Islamic Institute of Tulungagung and PGRI teacher training college of Tulungagung. 213 Javanese undergraduate students were selected based on two-step purposive sampling. To collect data, the researcher used observation and questionares in which the participants answered a set of 12 open-ended questions to measure the students’ term along with educational institution and Indonesian morphology-syntactical interference. To analyze the data, t-test on correlation and coefficient as well as linier stepwise multiple regressions were conducted through Statistical Package for Social Sciences (SPSS) version 17. Data analysis indicated that the independent variables significantly correlated with Indonesian morphology-syntactical interference. In addition, multiple regressions analysis specified different higher institution as the main contributing variable and students’ term as the second one on the arising of Indonesian interference. It also showed that students of English departments of state Islamic institution of Tulungagung got higher scores on the arising of Indonesian morphology-syntactical interference than those of PGRI teacher training college of Tulungagung. The reason may refer to the supporting environment that is higher language exposure. The results highlighted the longer the students’ term they have, the lower score on the arising of Indonesian morphology-syntactical interference they produce.